A Psychoanalytic Analysis of Mohamed Suleiman's Kiu. Issue 3 (2nd October 2019) - Mbarouk, Saade Said
ABSTRACT: This paper attempts to read Mohamed Suleiman Mohamed's novel Kiu through the psychoanalytical lenses. It demonstrates how psychoanalysis theory has been utilised in the analysis of the novel. The paper critically investigates how the tripartite parts of the psyche that motivate humans to act in different ways functions. It analyses how the author uses monologues, inner dialogues and dreams that portray the subconscious to build his characters and define their traits, and how any number of character traits are used to advance different themes in the novel. The paper also addresses how the presentation of ideas and narrative styles are used to capture the author's psychic unconsciousness and his worldview of life and actions in society, perspectives on human feelings and how dreams in the novel relate to psychoanalytical theory. The paper also points out how the reader and the critic are affected by texts that they read. The paper is premised on an analysis of moral states and outlooks on life that arise from actions related to the psyche.